Probabilistic aging - Dominik Grafenhofer; Christian Jaag; Christian Keuschnigg; Mirela Keuschnigg (Center for Economic Studies and ifo Institute (CESifo), 2006)
The paper develops an overlapping generations model with probabilistic aging of households. We define age as a set of personal attributes such as earnings potential, health and tastes that are characteristic of a person's position in the life-cycle. In assuming a limited number of different states of age, we separate the concepts of age and time since birth. Agents may retain their age characteristics for several periods before they move with a given probability to another state of age. Different generations that share the same age characteristics are aggregated analytically to a low number of age groups. The probabilistic aging model thus allows for a very parsimonious yet rather close approximation of demographic structure and life-cycle differences in earnings, wealth and consumption. Existing classes of overlapping generations models follow as special cases.
Keywords: J21; H55; D91; D58; 330; overlapping generations; aging; demographics; life-cycle earnings; Overlapping Generations; Alternde Bevölkerung; Bevölkerungsentwicklung; Lebenseinkommen; Theorie